Evaluation of the PVD and CVD coatings’ structure using the modified method of spherical metallographic microsection (Baltest-M). - Betiuk, Marek (International Conference on Plasma Surface Engineering, 2013)
The Baltest-M testing method developed at the Institute of Precision Mechanics allows a precise metallographic analysis of the structures of the coating and substrate materials subject to a strong local plastic strain. The material structure of locally strained areological systems (coating: PVD, CVD – substrate: steel, carbides) is revealed on precise spherical polished sections. The essence of this new testing method is the fact that the spherical polished sections are made in the area of indentations formed during hardness testing (HB, HRC, HV, HK of the surface) of the areological system. Material structures of substrate and coating in the indenter strain area are analysed quantitatively and qualitatively. The Kulotester test rig with a high-quality optical system, a rotary x-y bench for a sample holder and a microprocessor controller allows a precise preparation of polished sections within the indentations formed during the hardness test.